DINAMIKA PERTIMBANGAN TERHADAP PENGUSULAN DAN PERPANJANGAN PJ KEPALA DAERAH (STUDI KASUS KABUPATEN KAMPAR TAHUN 2023 - Aqil, Rafiq; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
To fill the vacant regional head position, Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors Article 201 paragraph 11 states that to fill the vacant position of regent/mayor, an acting regent/mayor is appointed from the high-ranking pratama leadership position until the inauguration of the regent/mayor. The mechanism for the process of proposing and extending the Acting Regional Head is questionable and has a strong political tendency. The reason is that among the names proposed by the Kampar Regency DPRD and also the Governor of Riau, it is necessary to consider carefully to become the acting regional head. This study aims to determine the consideration factors and mechanisms for the process of proposing and extending the Acting Regional Head. This study uses a study of the theory of visionary decision-making considerations in Rizki Eka Febriansah's book which consists of past, present and future factors. The method in this study uses a descriptive research type with a qualitative approach. Data sources consist of primary and secondary data collected through interviews and documentation. Data analysis uses qualitative data analysis techniques. The results of this study indicate that the process of proposing and extending the name of the Acting Regional Head is carried out with several considerations. Considerations from government experience, loyalty, and digital track record which are factors from the past. Considerations of performance both in terms of economy, social and culture which are factors from the present. Visionary considerations both from the vision and mission, long-term plans, and policies are factors from the future. The results of this study suggest that those who are entitled to become acting regional heads are people who understand the conditions of the region both from a social and cultural perspective, do not just propose people who are not suitable to become acting regional heads. Keywords: Mechanism, Dynamics of Consideration, Acting Regional Heads. Keywords: Village Government Strategy, Tourism Potential Management